PENGARUH IMPLEMENTASI KEBIJAKAN STANDAR NASIONAL PENDIDIKAN TERHADAP KUALITAS PELAYANAN PENDIDIKAN PADA SEKOLAH MENENGAH ATAS NEGERI DI JAKARTA SELATAN - Sanusi Sanusi (Indonesian Journal of Dialectics, 2012)
Research using qualitative deductive approach. Research informants as many as 6 people consisting of four officials of bureaucracy, a member of the legislature, and a public figure. Determination of research informants using snow ball technique. Secondary data collection using library research, document and observational studies. The collection of primary data using interview techniques. Processing the data using descriptive analysis method. From the discussion of the research results obtained the following conclusions:Regional Leadership of Banten Province is  leadership of the government that took place in the administration of the system of administration and development management. Regional Leadership of Banten Province actualized as a spokesman, as a direction setter, as a coach  and as change agent is an important roles in the leadership of the head region.